PRE-BREEDING RESEARCH ON BROAD BEAN (VICIA FABA L.) - I.T. Balashova (Ovoŝi Rossii, 2011)
Pre-breeding research on 20 accessions from collection of broad bean (Vicia faba L.) of All-Russian Research Institute of Vegetable Breeding and Seed Production has been performed. Four traits such as height of plan, height of stem from soil surface up to lowest bean (most important characteristics for mechanized harvesting), number of seeds in the bean, and the size of seeds were taken to be studied. Four promising accessions N 9, N 27, N 33, N 15d-vf18096 that have a set of three valuable characteristics, namely the high seed yield, large seeds, and great height of the stem from the soil surface up to lowest bean have been selected out at previous stage of breeding program.